Point dose measurement on center and peripheral target for stereotactic treatment using Helical Tomotherapy Hi-Art - Laras Ati Nur Fatimah; Nuruddin Nasution; Wahyu Edy Wibowo; Supriyanto Ardjo Pawiro (Journal of Medical Physics and Biophysics, 2018)
Stereotactic radiosurgery (SRS) and stereotactic radiotherapy (SRT) using tomotherapy were advanced radiotherapy technique with prescribing high dose on the peripheral target to get as steep as possible fall-off dose criteria on the target. These technique need an accurate and high precision treatment delivery also passing the criteria for patient specific quality assurance. Point dose measurement was a simple verification to ensure these goals. However, there are many issues for point dose measurement with ionisation chamber related to the problem of high dose gradient area on the peripheral target. Therefore, the purpose of this study was to verify the assessment criteria of ±3% discrepancies for center and peripheral target measurement. The work has been done by point dose verification for 11 patient with brain cancer using Helical Tomotherapy Hi-Art. Point dose measurement were done on the center and peripheral PTV, also brainstem for organ parameter in the off-axis area, using Exradin A1SL. The measurement results show that highest discrepancy compared to the dose plan for center and peripheral target reach 1.95% and 2.81%, respectively. The Higher discrepancies shows for peripheral target compared to the center target measurement. The measurement on the brainstem show a highest discrepancies reach 5.29%. This result occur because of the off-axis area of the brainstem location. In conclusion, the center and peripheral target measurement are meet the criteria ±3% by the dose plan with peripheral target measurement shows higher discrepancies influences by volume averaging effect and lack of particle equilibrium of the condition related to the chamber size.